(untitled) (Damascus University Journal for engineering sciences, 2021)
Experimental studies are the basis for obtaining the actual response of structures under seismic forces during earthquakes, this is very important when retrofitting existing structures that are vulnerable to earthquakes because of lack of compliance with modern seismic provisions and to design an earthquake resistant structures in the future. Nevertheless, the high cost of such experiments on actual structures or scaled models makes it unfeasible to conduct such experiments. Therefore, numerical modeling of structures that simulate the actual ones using numerical simulation methods such as finite element method became invaluable. However obtaining a numerical model of a structure needs to be validated against erroneous analysis results. In this research a validation study to compare the numerical simulation results with experimental results are needed. These experiments should be cost-effective to obtaining the desired results. Ambient vibration measurements followed by processing offered accurate dynamic properties of the structures. These properties are the basis in assessing the dynamic linear and nonlinear response of the structure under earthquakes. And thereby comparing the experimental results with the numerical simulation results validated the accuracy of the numerical model and justified the usage of it as it demonstrated the model to be accurate. The ambient vibration measurements which were performed in this research; and the numerical model which was developed gave satisfactorily close results when they were compared. In the numerical modeling methods two approaches were conducted. The first one is by performing a direct frequency extraction analysis i.e. vibration eigenvalue problem solving, and the second one is by performing a modal testing procedure on the response of the structure after applying seismic excitation on the building.